The role of internal audit function in strengthening corporate governance: a case on Yemeni commercial banks/ Abdulrahman Mohammed Al-yazidi, Md. Faruk Abdullah and Adeeb A. Alhebry - Mohammed Al-yazidi, Abdulrahman; Abdullah, Md. Faruk; A. Alhebry, Adeeb (Universiti Teknologi MARA Selangor, 2022)
This study examines the relationship between internal audit function (IAF) and the effectiveness of corporate governance (CG) in Yemeni commercial banks. The data were collected by a questionnaire survey distributed to internal auditors, heads of internal audit, chairman and members of audit committees, chief executives, and financial managers of Yemeni commercial banks. After distributing the questionnaire survey to the respondents, 158 valid questionnaires were obtained for analysis. Smart PLS 3 was used to analyse the data and test the hypotheses on the relationship between the attributes of the IAF and the effectiveness of CG. The study findings show a strong association between the efficacy of CG and the IAF's objectivity, independence, professional ethics, and IAF size. The results obtained represent a valuable addition to the literature on the attributes of IAF that affect the effectiveness of CG in developing countries, such as Yemen. Finally, the paper concludes that the attributes of the IAF have a significant and influential role in enhancing the effectiveness of CG.